Tuberculosis awareness [ La prevenciَn de la Tuberculosis / Coastal Health+Train (Coastal Training Technologies Corporation, 2005)
(Producer's website) Includes information on various aspects of TB including: how TB is contracted, symptoms of TB infection, what happens if one is infected by TB and and who is at risk